A mechanism for the dependence of sunspot group tilt angles on cycle strength - Işık, Emre (Iop Publıshıng Ltd, Temple Circus, Temple Way, Bristol Bs1 6Be, England, 2015)
The average tilt angle of sunspot groups emerging throughout the solar cycle determines the net magnetic flux crossing the equator, which is correlated with the strength of the subsequent cycle. I suggest that a deep-seated, non-local process can account for the observed cycle-dependent changes in the average tilt angle. Motivated by helioseismic observations indicating cycle-scale variations in the sound speed near the base of the convection zone, I determined the effect of a thermally perturbed overshoot region on the stability of flux tubes and on the tilt angles of emerging flux loops. I found that 5-20 K of cooling is sufficient for emerging flux loops to reproduce the reported amplitude of cycle-averaged tilt angle variations, suggesting that it is a plausible effect responsible for the nonlinearity of the solar activity cycle.
Keywords: Sun: activity; Sun: interior; Sun: magnetic fields; Sunspots; Magnetic-Flux Tubes; Convection Zone; Solar-Cycle; Base; Sun; Intensification; Overshoot; Envelope; Models